Public Libraries in Nineteen States 1987. Number of Libraries, Library Outlets, and Staff. E.D.TABS - Podolsky, Arthur; National Center for Education Statistics (ED), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
This report is based on information from the 1987 Federal/State Cooperative System for Public Library Data, which was collected in machine-readable format by the U.S. Department of Education's National Center for Education Statistics. Tables present the following data on public libraries in the 19 states that participated in data collection: (1) number of libraries by state, hours of service per week, and population served; (2) number of libraries by state, hours of service per week, and number and type of outlet; (3) number of libraries by size of population served, hours of service per week, and number and type of outlet; (4) number of libraries by state, hours of service per week, and type of staff; and (5) number of libraries by size of population served, hours of service per week, and number and type of staff. Each table also provides statistical totals. Notes on the data collection methodology, related reports, response rate, and definition of terms are included. States participating in the voluntary program were Colorado, Florida, Idaho, Indiana, Iowa, Minnesota, Montana, New Hampshire, New York, North Carolina, Ohio, Oklahoma, Oregon, Pennsylvania, South Carolina, Texas, Utah, Washington, and Wyoming. (MES)
ERIC Note: Data Series: DR-LIB-87/88-1.1.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Library Services; Library Statistics; Library Surveys; Public Libraries; State Libraries; Tables (Data); Numerical/Quantitative Data